SISTEM PENGOLAHAN NILAI SISWA BERBASIS WEB DI SMK NEGERI 1 SIJUNJUNG - Prima Zane, wahyu; novita, rini; kurniawan, haris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
SMK Negeri 1 Sijunjung is a vocational high school in Sijunjung Regency, West Sumatra Province. However, student grade processing is still done manually, resulting in a lack of efficiency in the current web-based student grade processing system. A suboptimal processing system can result in slow processing, input errors, and difficulties in accessing student grade information in real time. Furthermore, the current system may also lack interactivity and be difficult for all parties to access. The methodology used is the System Development Life Cycle (SDLC) with the waterfall model, which includes the stages of analysis, design, implementation, research, and development. Class data, subject data, student data, grade reports, and user data are all functions within this system. Alpha and beta testing of this information system were conducted. The results of the alpha testing indicated that the system functioned well and was valid. Beta testing results showed that expert validation (system experts) achieved an average score of 81.82%, with a very good rating, and user validation achieved an average score of 86.36%, with a very good rating. Therefore, it can be concluded that the web-based student grade processing system is suitable for use. Based on the research results, this information system can improve the efficiency and accuracy of grade management, as well as increase transparency through features that allow reports to be viewed by users and teachers. It is hoped that this web-based student grade processing system will be usable and facilitate teacher and user processing of student grades at SMK Negeri 1 Sijunjung.